The Relationship Of Hypnotherapy On The Knowledge Of Mothers Who Have Tantrum Children At The Rahma Midwifery Clink, Panyabungan Tonga District, Mandailing Natal District - Khoirunnisa’a Batubara; Ester Selfia Napitupulu (Jurnal EduHealth, 2021)
Tantrums are a person's inability to control emotions related to a decrease in tolerance for stress. Children usually express their emotions by crying and screaming as loud as possible, rebelling, kicking and even hurting themselves or others. In children's hypnotherapy, this technique is used to help children overcome tantrum behavior in a more positive way. The aim of the research was to determine the relationship between hypnotherapy and the knowledge of mothers who have tantrum children. The method used in this research is correlational research. The population in this study was around 37 patients who had tantrum children from the Rahma midwife clinic. The sampling technique uses Purposive Sampling. The sample in this study was 27 people. Data collection uses a questionnaire. Data analysis used the chi square test. The research results showed that the majority of respondents had sufficient knowledge, namely 14 people (50.0%) and the minority of respondents had good knowledge about hypnotherapy, namely 4 people (14.8%). The results of the chi square test analysis show that there is a significant relationship between hypnotherapy and the knowledge of mothers who have tantrum children at the Rahma Midwife Clinic, Panyabungan Tonga District, Mandailing Natal Regency based on mother's age (p=0.008), education (p=0.002), occupation (0.001) and information sources (p=0.010). The conclusion of this research is that there is a significant relationship between hypnotherapy and the knowledge of mothers who have tantrum children at the Rahma Midwife Clinic, Panyabungan Tonga District, Mandailing Natal Regency. It is hoped that health workers can provide education to parents about tantrums and proper and correct handling of tantrums.